Application of the digital twin concept for a distribution network - Wagner, Timo; Mehlmann, Gert; Richter, Michael (PESS 2020 - IEEE Power and Energy Student Summit, Conference Proceedings, 2020)
In this paper the development process of a digital twin in a real-time digital simulator (RTDS) is presented. The digital twin is based on a distribution grid section of the local distribution system operator ESTW AG. For automated import of load flow data in the digital twin a Python interface is programmed. The Python interface handles the import of the measurement data from the power grid monitoring software GridVis, which is the data management tool used by the distribution system operator, to the real-time digital simulator. After the successful implementation of the grid section in the real-time digital simulator as well as the automated data transfer, the load flow in RSCAD is validated by comparison of the load flow results of a corresponding offline load flow grid model in PSS™SINCAL. Finally, a Power Hardware-in-the-Loop (PHIL) test is set up to test different load scenarios.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Automatic data transfer; Digital twin; Power hardware-in-the-loop; Real-time digital simulator

Comparison of electromagnetic transient models for modular multilevel converters in high-voltage direct current applications - Tran, Kien-Nghiep; Richter, Michael (PESS 2020 - IEEE Power and Energy Student Summit, Conference Proceedings, 2020)
Modular multilevel converters (MMC) for high-voltage direct current (HVDC) transmission systems can contain up to several thousand submodules per HVDC station. Modeling each submodule in electromagnetic transient type simulations poses a computational challenge as the runtime increases significantly. To tackle this issue, different modeling concepts were developed which can reduce the simulation runtime drastically. This paper focuses on the Detailed Equivalent Model (DEM), the Switching Function Model (SFM) and the Average Value Model (AVM), which are capable of modeling a full scale HVDC system efficiently. To compare them, simulations of the steady state operation as well as the operation during different transient conditions are conducted in PSCADTM/EMTDCTM in conjunction with MATLAB™/Simulink™. Relevant quantities of the SFM and AVM are then validated against the DEM. The results show that the behavior of both, SFM and AVM, are very close to the DEM. However, the reaction of the AVM to sudden voltage or current changes, as in case of a fault event, differs greatly from the DEM. For the investigation of the DC pole-to-pole fault, the DEM block provided by PSCADTM has proven to be not working as expected.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Average value model; Detailed equivalent model; Electromagnetic transient (EMT) model; Modular multilevel converter; Modulation; Switching function model

Concept and Operation of a distributed multi-domain Power System Laboratory with HiL-capabilities - Mehlmann, Gert; Scheibe, Christian; Resch, Simon; Kordowich, Georg; Richter, Julian; Wagner, Timo; Kuri, Ananya; Richter, Michael; Jäger, Johann; Luther, Matthias (ETG-Fachbericht 170: ETG Kongress 2023, 2023)

Demonstration of Grid-Forming Controls in Hybrid AC/DC Grid in a Real-Time PHiL Environment - Richter, Michael; Kuri, Ananya; Richter, Julian; Wagner, Timo; Henninger, Stefan; Mehlmann, Gert (Electronics, 2025)
The transition to inverter-dominated power systems with novel control strategies has created weak grid scenarios, prompting extensive research into grid-forming (GFM) converters and advanced GFM control schemes. This study evaluates two GFM control strategies for their stabilizing effects in weakly interconnected and islanded power systems: the established Virtual Synchronous Machine (VSM) control and the newly developed Phase-Restoring Principle (PRP). The evaluation is conducted using a real-time electromagnetic transient (EMT) simulation testbed with Hardware-in-the-Loop (HiL) capabilities. The system includes a multi-terminal medium-voltage (MVDC) and high-voltage direct current (HVDC) network weakly coupled to a network equivalent, represented by a scaled synchronous machine (SynM) to replicate grid inertia. Modular multilevel converters (MMCs) model the converters, while Power Hardware-in-the-Loop (PHiL) experiments integrate real power hardware. Dynamic interactions, including islanded conditions, are emulated to assess the performance of GFM controls and their interactions in HV/MV and AC/DC systems. The results demonstrate the compatibility of diverse GFM schemes with grid-following controls and synchronous machines, emphasizing their positive contributions to system stability. This modular demonstrator, as a realistic prototype of future power systems, provides a flexible platform for testing emerging GFM strategies and hardware, supporting the development of robust and stable inverter-based grids.
CRIS-Team Scopus Importer:2025-03-14
Keywords: grid-following; grid-forming; HVDC; islanding; microgrid laboratory; MMC; MVDC multi-terminal; phase-restoring principle; PHiL; real time; virtual synchronous machine

Grid Code Compliant Modeling and Control of Modular Multilevel Converters during Unbalanced Faults - Richter, Michael; Mehlmann, Gert; Luther, Matthias (2019 54th International Universities Power Engineering Conference, UPEC 2019 - Proceedings, 2019)
This paper presents necessary modeling and control enhancements for Modular Multilevel Converters (MMC) to provide Fault-Ride-Through capability and fast fault current injection as required by the new German Technical Connection Rules for HVDC. HVDC converters have to be able to detect and control the grid voltage and grid currents accurately during all fault conditions. That applies to the positive as well as negative sequence components, hence a Decoupled Double Synchronous Reference Frame - Phase-Locked-Loop (DDSRF-PLL) and Current Control (DDSRF-CC) are implemented. In addition, an enhanced current limitation and an extension of the horizontal balancing control are proposed to complement the control structure for safe operation.
CRIS-Team Scopus Importer:2019-12-10
Keywords: Balancing Control; Converter Control Design; fast fault injection; Fault-Ride-Through Capability (FRT); Grid Codes; High Voltage Direct Current (HVDC); Modular Multilevel Converter (MMC); Technical Connection Rules (TCR)

Impact of recovery and sympathetic inrush phenomena on VSC HVDC systems - Richter, Michael; Mehlmann, Gert; Luther, Matthias (2022 57th International Universities Power Engineering Conference: Big Data and Smart Grids, UPEC 2022 - Proceedings, 2022)
The converter transformer of a VSC HVDC station can be driven into saturation caused by external grid events as short-circuits or the energization of nearby transformers. These effects are classified as inrush phenomena and named recovery inrush and sympathetic inrush, respectively. In this paper, a thorough study on different influencing factors on the inrush magnitude and its impact on the operation of the HVDC system is analyzed based on electromagnetic transient analysis using an average based EMT MMC HVDC model. As important parameters for the analysis of the recovery inrush the short-circuit ratio, the time point of fault inception and the fault duration, the fault distance and the fault resistance are selected. The impact of these parameters on the inrush intensity and the transients of the transformer and converter currents as well as active and reactive powers during the inrush events are analyzed and worst-case scenarios evaluated. By evaluation of internal converter signals, it is checked whether the converter is able to maintain stability for different inrush intensities.
CRIS-Team Scopus Importer:2022-11-25
Keywords: converter transformer saturation; HVDC; MMC; recovery inrush; sympathetic inrush

Integration of a Grid-Forming MVDC-System into a Transmission Grid Section for Real-Time Applications - Richter, Julian; Burlakin, Ilya; Wagner, Timo; Richter, Michael; Mehlmann, Gert; Luther, Matthias (8th IEEE Workshop on the Electronic Grid (eGrid 2023), 2023)
MVDC systems offer the possibility of bulk integration of renewable energies coupled at suitable nodes in transmission grids. However, some challenges still need to be solved for commercial use, such as appropriate control of the converter stations and interactions with existing AC equipment. This paper proposes a methodology to create a real-time AC Study Area with plausible short-circuit power and generically adjustable inertia provided by the surrounding area of an extended transmission network using dynamic External Area machines. An MVDC system with grid-forming control is installed in the Study Area, and the behavior of the MVDC system and the External Area machines is analyzed during frequency events at different grid strengths.<br
Keywords: MVDC; Grid-forming Control; Short-Circuit Power; Inertia

Integration of an EMT HVDC model into a Transient Stability Study using Co-Simulation - Scheibe, Christian; Richter, Michael; Raab, Alexander; Stopfer, Benedikt; Mehlmann, Gert (IEEE PES Innovative Smart Grid Technologies Conference Europe, 2022)
This paper provides insights into the development and application of coupling power system models within different simulation domains (phasor and instantaneous values) in a multi-instance manner using Co-Simulation. Overcoming the challenge of integrating a PSCAD modeled modular multilevel converter into the transient stability test model known as Nordic Test System, the Co-Simulation interface development and implementation process is laid out. Hybrid simulations are performed to verify the model and to investigate grid stabilizing effects of the converter in the RMS power system model. Results prove to the Co-Simulation to be a viable option, practically eliminating the need to re-model an existing EMT subsystem for this kind of studies.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Co-Simulation; EMT; HVDC; MMC; RMS

Potential and Challenges of DC Distribution Grids to Mitigate RES Volatility Effects and Provide System Services in AC Grids - Richter, Julian; Richter, Michael; Müller, Moritz; Mehlmann, Gert; Luther, Matthias (IEEE PES GM 2024, 2024)
Based on various system simulations, this paper discusses combining renewable energy systems (RES) and battery energy storage systems using DC grids. The concept comprises the mitigaton of effects induced by RES volatility and provide reliable power injection which allows the provision of system services. To demonstrate the technical potential and fields of application of these DC grids in short and long time frames, a DC collector grid and an MVDC link are investigated in the RMS and EMT domain, respectively. The results show that the proposed DC grids are able to provide plannable power infeed into existing AC grid structures. Only slight deviations depending on the control strategy and the converter model detail occur during extrem RES power gradients. After the validation of the technical potential, different challenges of these DC grid applications are discussed.<br
Keywords: BESS; DC-Grids; RES; System Services

Potential of Modular Multilevel Converter Technology providing Synthetic Inertia and AC Frequency Support for AC Grids - Porst, Johannis; Richter, Michael; Biller, Martin; Luther, Matthias (NEIS 2020 - Conference on Sustainable Energy Supply and Energy Storage Systems, 2020)

Validation of a modular multilevel converter with additionally integrated energy storage for grid-supportive operation - Richter, Michael; Klein, Konstantin; Luther, Matthias (6th IEEE International Energy Conference, ENERGYCon 2020, 2020)
For the successful energy transition, the Modular Multilevel Converter (MMC) serves as an attractive solution for HVDC power transmission. Within this paper, the partial integration of additional energy storage elements into the underlying structure of the converter is presented. By extending a certain proportion of the submodules to form energy storage modules, the resulting Energy-Storage MMC is capable of storing or releasing an additional portion of its rated power on the AC-side without the need to adjust the DC power flow. The design of this topology and the necessary modifications for the control structure are studied. The property of storing or releasing additional power during normal operation enables the converter to provide grid-supportive functions. The ES-MMC concept is validated by conducting appropriate dynamic simulations in MATLAB® Simulink®. For this purpose, its participation in the frequency containment process and in power oscillation damping is examined in the Kundur two-area test system.
CRIS-Team Scopus Importer:2020-12-11
Keywords: Energy storage; Frequency support; Grid-booster; Grid-supportive function; HVDC; Modular Multilevel Converter; Power oscillation damping